(untitled) (Historia, 2021)
The recognition of customary law by the South African Republic. Several authors have claimed that blacks in the South African Republic were governed according to Roman Dutch law, that customary law was not recognised before 1877, and that this legal system was only recognised for the first time after the British annexation of the Transvaal in 1877. Although the official policy of the Republic was that blacks should be governed according to the laws of the country also applying to whites, in actual fact customary law was applied in the Zoutpansberg district since the 1860’s and in some respects throughout the Republic since 1876. That this was the case is apparent from a letter of President M W Pretorius to the Superintendent of Native Tribes in Zoutpansberg in 1865. The recommendations of a commission of 1871 appointed to investigate memorials pertaining to black servants and laws applying to blacks also confirm this. Furthermore, Law No 3 of 1876 seems to recognise indigenous law by implication by not prohibiting "the buying of wives" and poligamy, but by simply stating that these practices would not be recognised by the laws of the country. In this law, moreover, the Native commissioners were instructed to take cognisance of the customs of the blacks when acting as justices of the peace. Although there was therefore no law which accorded statutory recognition to customary law there can be little doubt that such law was indeed recognised in certain respects by the Republic by 1876. Hoewel verskeie skrywers reeds aandag aan die kwessie van die erkenning van inheemse reg deur die Zuid-Afrikaansche Republiek voor die Britse anneksasie van die Republiek in 1877 bestee bet, bestaan daar nog geen duidelikheid oor die aangeleentheid nie. Die rede hiervoor is waarskynlik omdat dit nog altyd as ’n onderdeel van ’n groter tema aangesny en nog nie as ’n selfstandige tema behandel is nie. In 1924 het E.H. Brookes, en na hom verskeie ander skrywers, hoofsaaaklik na aanleiding van ’n opmerking van Henrique Shepstone, die Sekretaris van Naturellesake in Transvaal gedurende 1877-1881, aangevoer dat voor die anneksasie van die Republiek die Swartes volgens die Romeins-Hollandse Reg regeer is, dat inheemse reg nie erken is nie en dat daar eers gedurende die Britse bewind in Transvaal erkenning aan hierdie regstelsel verleen is. In 1936 het J.D. Huyser verklaar dat die Zuid-Afrikaansche Republiek inheemse reg in ’n sekere mate erken het. Veertien jaar later het T.S. van Rooyen aangevoer dat dit die uitgesproke beleid van die Republiek was om die Swartes volgens naturellewet en gewoontes te straf. Die feit dat Van Rooyen sy bewering baseer op dokumente waarvolgens die Britse Regering erkenning aan inheemse reg in Transvaal verleen het, plaas sy opmerking onder verdenking. Hierdie artikel het dus ten doel om die aangeleentheid weer eens in oenskou te neem en aan te toon dat inheemse reg reeds in 1876 in sekere opsigte deur die Zuid-Afrikaansche Republiek erken is.